2018
DOI: 10.21037/atm.2018.10.61
|View full text |Cite
|
Sign up to set email alerts
|

Prevalent osteoporotic vertebral fractures more likely involve the upper endplate than the lower endplate and even more so in males

Abstract: Background: While the importance of identifying osteoporotic vertebral endplate fracture (EPF) is being recognized; the pathophysiological understanding of EPF till now remain insufficient. In this populationbased cross-sectional radiograph study, we aim to investigate the anatomic location characteristics of osteoporotic EPF. Methods: This study analyzed the anatomical location of osteoporotic EPFs in elderly Chinese population (age ≥65 years). The T4-L4 radiographs of 1,954 elderly Chinese men (mean: 72.3 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
26
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 44 publications
1
26
1
Order By: Relevance
“…We showed that except traumatic EPF involved both sEP and iEP, only approximately 1.9% involved iEP alone. This results contrast with osteoporotic EPF results, [ 19 ] where for singular EPF (only one EP in a vertebra), the ratio of superior EPF occurrence to inferior EPF occurrence was 9.63 (9.8% involved iEP) for males and 4.3 (17.4% involved iEP) for females. Thus iEP is more weakened during osteoporosis such that inferior EPF is relatively more common in osteoporotic VF than traumatic VF.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…We showed that except traumatic EPF involved both sEP and iEP, only approximately 1.9% involved iEP alone. This results contrast with osteoporotic EPF results, [ 19 ] where for singular EPF (only one EP in a vertebra), the ratio of superior EPF occurrence to inferior EPF occurrence was 9.63 (9.8% involved iEP) for males and 4.3 (17.4% involved iEP) for females. Thus iEP is more weakened during osteoporosis such that inferior EPF is relatively more common in osteoporotic VF than traumatic VF.…”
Section: Discussioncontrasting
confidence: 71%
“…Traumatic EPF features are then compared with the features of osteoporotic EPF as recently detailed by us. [ 13 , 14 , 16 , 18 , 19 ]…”
Section: Discussionmentioning
confidence: 99%
“…Genant et al assumed that endplate fracture is 100% sensitive for osteoporotic fracture (46), but ABQ approach not include anterior cortex buckling which is quite common as VF sign (Figure 3) (51). Furthermore, endplate fracture does not always occur at the center of endplate (52). Finally, the ABQ do not take account for grading the extent of vertebral height loss.…”
mentioning
confidence: 99%
“…Compared with those of conservative treatment, the outcomes of PV have been reported to benefit patients, thus providing better pain relief. However, the beneficial effects of PV have been reported to be associated with a higher incidence of new ASFs compared to conservative treatment [1][2][3][4][5][6][7][8] . Studies have reported that PV is not Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…OTFs can also be managed by percutaneous vertebroplasty (PV) or percutaneous kyphoplasty (PK). Both treatments are not perfect, and although various studies have described the outcomes and complications of each treatment, there is still no consensus on the optimal treatment regimen for OTFs 7,8 . Our study was a retrospective analysis that reported a series of OTF patients treated with PV, and it investigated the risk factors for adjacent segmental fractures (ASFs) based on the assessment of fractured vertebral kyphosis alignment on plain radiography and magnetic resonance imaging (MRI).…”
mentioning
confidence: 99%